2013
DOI: 10.1021/la403356j
|View full text |Cite
|
Sign up to set email alerts
|

Water-in-Water Emulsions Based on Incompatible Polymers and Stabilized by Triblock Copolymers–Templated Polymersomes

Abstract: Aqueous solutions containing a mixture of polyethylene glycol (PEG) and dextran homopolymers form an aqueous two-phase system which can be emulsified to give a water-in-water emulsion. We show how these emulsions can be stabilized using triblock polymers containing poly[poly(ethylene glycol) methyl ether methacrylate] (PEGMA), poly (n-butyl methacrylate) (BuMA), and poly[2-(dimethylamino) ethyl methacrylate] (DMAEMA) blocks of general structure Pp-Bb-Dd, in which the middle BuMA block is hydrophobic. Low-energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 40 publications
2
60
0
Order By: Relevance
“…However, no detailed description of the mechanism could be given. Buzza, Fletcher, Georgiou and Ghasdian, (2013) showed that tri-and diblock copolymers can be used to stabilize D/P and P/D emulsions at neutral pH. Phase inversion was observed at approximately the same volume fraction as in presence of protein microgels.…”
Section: Ph-induced Stabilization and Destabilizationmentioning
confidence: 99%
“…However, no detailed description of the mechanism could be given. Buzza, Fletcher, Georgiou and Ghasdian, (2013) showed that tri-and diblock copolymers can be used to stabilize D/P and P/D emulsions at neutral pH. Phase inversion was observed at approximately the same volume fraction as in presence of protein microgels.…”
Section: Ph-induced Stabilization and Destabilizationmentioning
confidence: 99%
“…The much smaller interfacial tensions and less obvious wettability preferences at aqueous/aqueous as compared to oil/water interfaces makes stabilizing water-in-water emulsions more challenging. Nonetheless water-in-water Pickering emulsions stabilized by latex beads 42, 43 , protein particles 44 , triblock copolymers 45 , and synthetic clay particles 40 have been produced.…”
Section: Introductionmentioning
confidence: 99%
“…For water-in-oil systems, emulsification is routinely accomplished using amphiphilic surfactants that adsorb at the water/oil interface. This approach, while not impossible for ATPS 20,21 , is much more challenging due to the chemical similarity of the two aqueous media. An alternative means of stabilizing a liquid/liquid interface is adsorption of particles to form a Pickering emulsion 22 .…”
mentioning
confidence: 99%